THE TEACHING OF ENGLISH SPEAKING SKILL AT “FIRST COURSE”: A CASE STUDY AT A BOARDING COURSE - Usman Efendi (Widya Mandala Surabaya Catholic University, 2016)
This research was to investigate the teaching of English speaking skill at “First Course”: at a boarding course in Bangkalan. This research is a descriptive case study of First Course. The subject of this research was two instructors who taught the book two level at First Course. The data of this research was the information that researcher collected from the result of interview and observation. The sources of data were the instructors and classroom activities. The instructor collected the data by using interview guide, observation sheet and field note. The information was in the form of the interview transcript and classroom observation (field note). The analysis of the research data resulted in several findings concerning the preparation of the teaching of English speaking skill and the implementation of the preparation on the teaching of English speaking skill at First Course that covered lesson plan, material and media, teaching techniques, assessment and evaluation, and assignment. The instructors not only taught English speaking to the students but also built the good students’ character. They improved morality, trained and strengthened spirit, appreciated the religious values, and taught attitude, politeness, discipline, diligence, honesty, responsibility, democratic, work hard, etc. Character education is one of way to build good characters and personality to the students of First Course in learning English.